Generalized Liver- and Blood-Derived CD8+ T-Cell Impairment in Response to Cytokines in Chronic Hepatitis C Virus Infection. - Stephanie C Burke Schinkel; Lorna Carrasco-Medina; Curtis L Cooper; Angela M Crawley (PLoS ONE, 2016)
Generalized CD8+ T-cell impairment in chronic hepatitis C virus (HCV) infection and the contribution of liver-infiltrating CD8+ T-cells to the immunopathogenesis of this infection remain poorly understood. It is hypothesized that this impairment is partially due to reduced CD8+ T-cell activity in response to cytokines such as IL-7, particularly within the liver. To investigate this, the phenotype and cytokine responsiveness of blood- and liver-derived CD8+ T-cells from healthy controls and individuals with HCV infection were compared. In blood, IL-7 receptor α (CD127) expression on bulk CD8+ T-cells in HCV infection was no different than controls yet was lower on central memory T-cells, and there were fewer naïve cells. IL-7-induced signalling through phosphorylated STAT5 was lower in HCV infection than in controls, and differed between CD8+ T-cell subsets. Production of Bcl-2 following IL-7 stimulation was also lower in HCV infection and inversely related to the degree of liver fibrosis. In liver-derived CD8+ T-cells, STAT5 activation could not be increased with cytokine stimulation and basal Bcl-2 levels of liver-derived CD8+ T-cells were lower than blood-derived counterparts in HCV infection. Therefore, generalized CD8+ T-cell impairment in HCV infection is characterized, in part, by impaired IL-7-mediated signalling and survival, independent of CD127 expression. This impairment is more pronounced in the liver and may be associated with an increased potential for apoptosis. This generalized CD8+ T-cell impairment represents an important immune dysfunction in chronic HCV infection that may alter patient health.